BS EN 60947-5-3. Low-voltage switchgear and controlgear. Part 5-3. Control circuit devices and switching elements. Requirements for proximity devices with defined behaviour under fault conditions (PDDB) (5th May 2022) - British Standards Institution,
No abstract available